KERAJAAN ALLAH DALAM DUA WAJAH Datangnya Ratu Adil dan Kerajaan Allah - Stepanus Istata Raharjo (P3TK, Sanata Dharma University, 2014)
The javanese mysticism (Kejawen) reflects a kind of messianic idea of a just king(Ratu Adil)that can be compared to the notion of